Comprehensive review on the application of inorganic and organic photovoltaics as greenhouse shading materials - Li, Lu; Ya’acob, Mohammad Effendy; Anuar, Mohd Shamsul; Mohtar, Mohd Nazim (Elsevier, 2022)
Agrivoltaic greenhouse is a win–win concept which is a creative integration between agriculture and Photovoltaic infrastructures to address the land use competition between solar PV and agriculture especially for anti-seasonal plants. PV shading on the greenhouse roof has attracted more attention in recent years especially in high insolation regions. Heat stress is an inevitable issue that almost exclusively contributed by near-infrared radiation (NIR) and thus affects the microclimate and plant growth of greenhouse. As the emerging PV technology, the absorption spectrum in the active layer of semi-transparent organic PV (OPV) is tunable and extends to NIR range through material selection thus, reduce excess solar heat stress on the plant. Herein, this paper reviews the major studies about different PV materials used in greenhouse roofing at various countries around the world for the last ten years (2010–2020). The development trend of different PV materials on the application of greenhouse could be observed. Active layer materials of OPV with strong NIR absorption and strong visible light transmittance are preferred owing to boosting times of usage and various benefits e.g., non-toxic, flexibility, lowest both on carbon footprint and energy payback time, thus becoming an ideal candidate as greenhouse shading material.